Vitamin D status of healthy coastal fishermen of Bangladesh (IMC Journal of Medical Science, 2020)
Background and objectives: Vitamin D deficiency is now a global concern. Industrialization, urbanization and the decreasing participation in outdoor activities, with consequent sunlight deprivation, are thought to be the key factors in the increasing prevalence of vitamin D deficiency among general population of many countries. It is presumed that healthy, adequately sun-exposed people should maintain adequate vitamin D levels. However, studies within this population are scarce. Hence, this study was conducted to find out the actual vitamin D status in healthy, adequately sun-exposed population living in coastal district of Bangladesh.Material and Methods: One hundred and forty healthy fishermen living in costal district of Cox’s Bazar (210 25' North, 910 59' East) of Bangladesh were enrolled in this study. Relevant data and blood samples were collected during August 2018, one of the months with lower zenith angle and higher UV index. Chemiluminescent micro-particle immunoassay (CMIA) was used to measure 25-hydroxy vitamin D3. Other relevant biochemical parameters measured were random blood glucose (RBG), serum creatinine, albumin, calcium, phosphate, alkaline phosphatase and intact parathyroid hormone (iPTH).Results: Mean vitamin D level of the study population was 27.04±7.20 ng/ml. Based on the cut off value of Endocrine Society, 70.7% of the study population had low vitamin D levels of which 26 (18.6%) and 73 (52.1%) were in vitamin D deficient (.05, 95%CI= -5.68226, 1.21086).Conclusion: The unexpectedly high prevalence of vitamin D deficiency in this healthy and adequately sun-exposed population raises the question regarding the validity of the current cutoff value being used to assess the vitamin D status of Bangladeshi population. Future studies should be carried out to determine nation-specific, local cutoff values for vitamin D sufficiency.Ibrahim Med. Coll. J. 2019; 13(2): 35-39